Roles of cell adhesion and adhesion regulatory proteins during collective cell migration and invasion - Kotian, Nirupama Somappa (Kansas State University, 2022)
Collective cell migration is the highly dynamic and coordinated movement of groups of cells. Various types of collectives are crucial for embryogenesis, neural crest migration, mammary gland development and wound healing. Collective cell movements are also found in cancer, which leads to tumor spreading and invasion to secondary sites in the body. These tumor collectives are efficient at invading deeper into tissues and enhance resistance to available therapies. Cells in collectives are tightly connected to each other through cell-cell contacts, which allows the cells to stay together during migration. The cellular and molecular mechanisms that regulate cell-cell communication and adhesion during collective cell migration and collective tumor cell invasion are not well understood. Cell adhesion and adhesion-regulatory proteins therefore are strong candidates to regulate collective cell behaviors. In this thesis, I used the Drosophila ovary border cell system to identify mechanisms that regulate cell-cell adhesion during collective cell migration in vivo. The ovary is made of repeating subunits called egg chambers. Each egg chamber is enveloped by a monolayer of follicular epithelial cells that surround the oocyte, nurse cells and a pair of polar cells on each end. During oogenesis, the anterior polar cells recruit 4-6 neighboring epithelial follicle cells to form the migratory border cell cluster. Border cells migrate through the dense nurse cell environment using guidance cues to reach their final target, the oocyte. This is an excellent, genetically tractable in vivo system to study conserved regulators of collective cell migration and invasion including cancer. Collective cell invasion is also observed in the primary malignant brain tumor glioblastoma. These cancer collectives are highly invasive and spread into the brain parenchyma leading to disease progression and poor patient prognosis. I performed a glioblastoma-related genetic screen to identify novel cell adhesion and adhesion regulatory proteins that contribute to collective border cell migration and brain tumor invasion. I identified eight adhesion genes that disrupted border cell collective migration when knocked down: α-catenin (α-Cat), Symplekin (Sym), Lachesin (Lac), roughest (rst), dreadlocks (dock), Wnt4, dachsous (ds), and fat (ft). Bioinformatics analyses showed that subsets of the orthologous genes were enriched at the invasive edge of human glioblastoma patient tumors. Next, I demonstrated two mechanisms through which adhesion proteins are regulated during collective border cell migration. First, I showed that small GTPase Rap1 mediates E-cadherin distribution at border cell-border cell contacts during collective migration. Additionally, I found that Rap1 is spatially regulated in the border cell cluster by the conserved GTPase activating protein, Rapgap. Next, I correlated crosstalk between protein phosphatase 1 (Pp1) and the cadherin-catenin complex during collective cell migration. Further, knocking down α-catenin and other members of the cadherin-catenin complex in border cells caused the cluster to dissociate and fail to migrate. Through these experiments, I thus identified a role for the cadherin-catenin complex in keeping border cells attached to each other during migration. Pp1 promotes levels of cadherin-catenin complex members at cell-cell junctions and keeps the cells in the cluster connected. Overall, in my thesis I provide insights into conserved mechanisms that mediate collective cell migration and collective cancer cell invasion through cell adhesion proteins.
Keywords: Cell adhesion; Collective cell migration; Collective cell invasion; Tumor models; Glioblastoma; Drosophila border cells